Answer:
27 degrees
Step-by-step explanation:
We are given that Angle AEF is 63. We can also see that EAF is a right angle. Since angles in a triangle add up to 180, we can use this to solve for AFE:
Angle AEF + EAF + AFE = 180
63 + 90 + AFE = 180
153 + AFE = 180
AFE = 27
<em>Or we can solve it another way</em>
Since EAF is a right angle, the other angles are complementary (they add up to 90) so...
Angle AEF + AFE = 90
63 + AFE = 90
AFE = 27
Answer:
We multiplu5(14-23)which will vive us 115-70 equivalent to -45 and then we divide 8÷2which will give us 4. Finally we add -45+4=-41
Step-by-step explanation:
Step-by-step explanation:
![8. log_{10}(2.15) = 0.332 \: then \: log_{10}(21500) = ..... \\ log(21500) = log(2.15 \times 10000) \\ = log(2.15) + log(10000) \\ = log_{10}(2.15) + log_{10}( {10}^{4} ) \\ = 0.332 + 4 log_{10}(10) \\ = 0.332 + 4(1) \\ log_{10}(21500) = 4.332](https://tex.z-dn.net/?f=8.%20%20log_%7B10%7D%282.15%29%20%20%20%3D%200.332%20%5C%3A%20then%20%5C%3A%20%20%20log_%7B10%7D%2821500%29%20%20%20%3D%20.....%20%5C%5C%20%20log%2821500%29%20%20%3D%20%20log%282.15%20%5Ctimes%2010000%29%20%20%5C%5C%20%20%20%3D%20%20log%282.15%29%20%20%2B%20%20log%2810000%29%20%20%5C%5C%20%20%20%3D%20log_%7B10%7D%282.15%29%20%20%2B%20%20log_%7B10%7D%28%20%7B10%7D%5E%7B4%7D%20%29%20%20%5C%5C%20%20%3D%200.332%20%2B%204%20log_%7B10%7D%2810%29%20%20%5C%5C%20%20%3D%200.332%20%2B%204%281%29%20%5C%5C%20%20log_%7B10%7D%2821500%29%20%20%3D%204.332)
9. log(2)=a, log(3)=b, then log(36)=______
log(36) = log(6*6) = log(6) + log(6)
log(36)= log(6) + log(6)
log(36) = log(3*2) + log(3*2)
log(36) = (log(3) + log(2)) + (log(3) + log(2))
log(36) = (a + b) + (b + a)
log(36) = a + b + b + a
log(36) = 2a + 2b
Refrection of point (0, 0) across y = 3 gives point (0, 6)
Refrection of point (0, -6) across the x-axis gives point (0, -6)
Answer:
47
Step-by-step explanation:
Let's solve your equation step-by-step.
−4x−3(−44−23)=13
Step 1: Simplify both sides of the equation.
−4x+201=13
Step 2: Subtract 201 from both sides.
−4x+201−201=13−201
−4x=−188
Step 3: Divide both sides by -4.
−4x
−4
=
−188
−4
x=47